Musical Analysis Structure and Violin Playing Technique in Suzuki Violin Book - Riyadi, Lanang; Yensharti, Yensharti (Universitas Negeri Surabaya, 2023)
This article aims to describe and provide an overview of the analysis of the musical structure and violin playing techniques contained in the works in Suzuki Violin Book Volume 1. The research contained in this article uses a qualitative method with a systematic content analysis approach, objectivity, and generalization. The works analyzed in this research are